Strategic Planning of BUMDes in Kemamang Village: Management and Development Analysis - Ekowati, Wida; Hany Fanida , Eva (IDFoS Indonesia, 2024)
Law Number 6 of 2014 defines a village as a legal community unit with the authority to manage governance and local interests based on community initiatives, ancestral rights, and traditional rights recognized within Indonesia's governance system. Villages are expected to establish economic entities such as Village-Owned Enterprises (BUMDes) to promote rural economies, as outlined in Article 87 of the law. BUMDes Sembodo in Kemamang Village was established in 2018, starting with a retail business and an initial capital of IDR 40,000,000 from the village. It was later expanded to include waste management. In 2022, BUMDes Sembodo received IDR 100,000,000 in Special Financial Assistance (BKK), but the funds have not been fully utilized. The management intended to use these funds to develop the BUMDes for the welfare of the village community. Proper management of these funds could increase village revenue and provide significant benefits, making it crucial to maximize their use. This research applied Grindle’s theory, dividing strategic management into Human Resource Strategy, Organizational Strengthening Strategy, and Institutional Reform Strategy. A qualitative method was used, including observation, interviews, documentation, and references from journals and previous research. Findings showed that BUMDes Sembodo’s management has strong human resources, supported by Village Government training. However, participation in forums remains limited. Most managers hold bachelor’s degrees, with some having only high school diplomas. The organizational development of BUMDes Sembodo needs strengthening through regular consultation activities, and collaboration with third parties has not yet occurred.